Pathway to sustainability: the Marine Stewardship Council certification standard as an improvement framework for African fisheries - Oloruntuyi, Oluyemisi; Barendse, Jaco; Marriott, Michael; Gordon, Andrew Kenneth; Montero-Castaño, Carlos (Frontiers in Marine Science, 2023)
Fishery certification is increasingly employed as a multi-stakeholder, market-based mechanism to promote sustainability of fisheries. Preparing for, and achieving certification continues to deliver tangible improvements and benefits to fisheries, but the number of certified fisheries from Africa remains low. Some of the factors that constrain certification of fisheries in the region include limited data to assess and manage fisheries, the open access nature of many fisheries, overfishing, poor management, inadequate enforcement, and low demand for certified seafood. To overcome these constraints, several fisheries employ a “pathway to sustainability” approach that involves using the MSC fisheries standard as a framework for gap analysis, action planning, progress tracking and improvement. Certification may not always be the goal. This allows fisheries to make ongoing improvements over prior performance, regardless of whether they immediately achieve certification or not. Progress towards the desired goal, sustainable management, can be tracked over time. Some of the reported benefits include clarity of objectives, consolidation and focus of stakeholder efforts, participatory engagement, ability to attract resources for improvements, benchmarking of performance and, ultimately, improved environmental performance through better fisheries management. This paper discusses the uptake of this approach in Africa, by presenting case study fisheries from the continent. It outlines mechanisms through which these fisheries embarked on a pathway to sustainability using the MSC fisheries standard, and the outcomes from these initiatives. It highlights the successes and challenges associated with implementation. The paper concludes that the MSC standard and the improvements that it incentivizes can make a positive contribution to regional efforts to improve environmental sustainability, fisheries governance and consequently the socio-economic viability and resilience of fisheries in Africa.